M?todos de interpola??o para sistemas OFDM - Rocha, Carlos Augusto (2011)
The OFDM technique has been the aim of studies and researches in institutions all over the world. Its last applications are in Digital TV Systems like: the DVB- T, the ISDB-T and also in wireless systems, such as: Wi-Fi and Wi-Max. One of the greatest limitations of the OFDM technique?s use is the necessity of main- taining the synchronism between the N oscillators of reception and transmission systems, due to the orthogonality among the subcarriers. With the signal?s dig- ital processors? improvement, it became possible to solve this problem through the IFFT/FFT?s use. This work aims to present the equalizations? basic techniques used in modu- lations with multiple carriers. The OFDM signal?s symbols are subjected to the interferences during the transmission process due to the multiple routes of the channel and to the impulsive noises. The results of those interferences are the rotation and the constelation?s amplitude alteration. Then, it is necessary the inclusion of the pilot carriers in the transmission system, estimating the channel response in the frequency of each sub-carrier. In this study it was analysed four interpolation techniques to obtain the chan- nel?s frequency response. Through simulations, it was also arisen the respective performances. It was used the linear, cubic, FIR and FFT interpolations. An anl- ysis of each interpolation?s technique?s efficiency is presented, using some pattern channels for test with diverse characteristics.